MAIN TENDENCIES IN ANESTHESIOLOGY DEVELOPMENT FOR THE LAST 10 YEARS - V. V. Likhvantsev (Вестник анестезиологии и реаниматологии, 2019)
The article describes the main tendencies in anesthesiology, which have undergone the greatest changes in the last decade, according to the author. The article speculates on the choice of tactics and the qualitative components of peri-operative infusion therapy. The author gives an assessment of the current stage of studying the phenomenon of anesthetic preconditioning and acute heart failure management. And, finally, the challenges and achievements of the evidence-based medicine in anesthesiology are analyzed.